Laser circular cutting of Kevlar sheets: Analysis of thermal stress filed and assessment of cutting geometry - Yilbas, B.S.; Akhtar, S.S.; Karatas, C. (Elsevier BV, 2017)
Abstract A Kevlar laminate has negative thermal expansion coefficient, which makes it difficult to machine at room temperaures using the conventional cutting tools. Contararily, laser machining of a Kevlar laminate provides advantages over the conventional methods because of the non-mechanical contact between the cutting tool and the workpiece. In the present study, laser circular cutting of Kevlar laminate is considered. The experiment is carried out to examine and evaluate the cutting sections. Temperature and stress fields formed in the cutting section are simulated in line with the experimental study. The influence of hole diameters on temperature and stress fields are investigated incorporating two different hole diameters. It is found that the Kevlar laminate cutting section is free from large size asperities such as large scale sideways burnings and attachemnt of charred residues. The maximum temperature along the cutting circumference remains higher for the large diameter hole than that of the small diameter hole. Temperature decay is sharp around the cutting section in the region where the cutting terminates. This, in turn, results in high temperature gradients and the thermal strain in the cutting region. von Mises stress remains high in the region where temperature gradients are high. von Mises stress follows similar to the trend of temperature decay around the cutting edges.